Ezra, Nehemiah, and Esther : restoring the church - Benn, Wallace; Hughes, R. Kent, 1942- (Wheaton, Illinois : Crossway, 2021)
"These neglected books of the Bible teach us about God's steadfast love toward his people and his deliverance of them. They are about how God keeps his promises and restores his Old Testament people after the sad and difficult years of the Exile"--
Our God reigns : see God (Ezra 1) -- The church family matters : see the church (Ezra 2) -- First things first : returning to worship (Ezra 3) -- Facing the battle (Ezra 4, 5, 6:1-12) -- The temple finished and dedicated (Ezra 6:13-22) -- "Lord, please do it again" (Ezra 7) -- Believers face challenges (Ezra 8) -- The danger of dilution (Ezra 9) -- Holiness matters (Ezra 10) -- A good heart for God and his work (Nehemiah 1) -- Making the most of the opportunity (Nehemiah 2:1-10) -- Sharing the vision and starting the work (Nehemiah 2:11-20) -- The family of God at work (Nehemiah 3:1-32) -- Getting the work completed (Nehemiah 4, 5, 6, 7:1-4) -- The importance of continuity (Nehemiah 7: 5-73a) -- Revival (Nehemiah 7:73b-8:18) -- Recounting the goodness of God (Nehemiah 9:1-37) -- Renewing the covenant (Nehemiah 9: 38-10:39) -- Recreating community (Nehemiah 11:1-36) -- A joyful celebration and a new beginning (Nehemiah 12:1-47) -- Broken promises (Nehemiah 13:1-31) -- Some final thoughts on Nehemiah -- Leadership lessons from Nehemiah -- The selection of Esther as queen (Esther 1-2) -- The plot to destroy the jews (Esther 3-4) -- The reversal of "fortune" begins (Esther 5-7) -- Deliverance for the Jews (Esther 8- 9) -- Some final thoughts on Esther (Esther 10).
Includes bibliographical references and indexes.
Keywords: Bible. -- Criticism, interpretation, etc; Bible. -- Criticism, interpretation, etc; Bible. -- Criticism, interpretation, etc; Bible. -- Criticism, interpretation, etc